Continuity of care is an important and distinct aspect of childbirth experience: findings of a survey evaluating experienced continuity of care, experienced quality of care and women's perception of labor - Hilde Perdok; Corine J. Verhoeven; Jeroen van Dillen; Tjerk Jan Schuitmaker; Karla Hoogendoorn; Jolanda Colli; François G. Schellevis; Ank de Jonge (BMC, 2018)
Abstract Background To compare experienced continuity of care among women who received midwife-led versus obstetrician-led care. Secondly, to compare experienced continuity of care with a. experienced quality of care during labor and b. perception of labor. Methods We conducted a questionnaire survey in a region in the Netherlands in 2014 among 790 women after they gave birth. To measure experienced continuity of care, the Nijmegen Continuity Questionnaire was used. Quality of care during labor was measured with the Pregnancy and Childbirth Questionnaire, and to measure perception of labor we used the Childbirth Perception Scale. Results Three hundred twenty five women consented to participate (41%). Of these, 187 women completed the relevant questions in the online questionnaire. 136 (73%) women were in midwife-led care at the onset of labor, 15 (8%) were in obstetrician-led care throughout pregnancy and 36 (19%) were referred to obstetrician-led care during pregnancy. Experienced personal and team continuity of care during pregnancy were higher for women in midwife-led care compared to those in obstetrician-led care at the onset of labor. Experienced continuity of care was moderately correlated with experienced quality of care although not significantly so in all subgroups. A weak negative correlation was found between experienced personal continuity of care by the midwife and perception of labor. Conclusion This study suggests that experienced continuity of care depends on the care context and is significantly higher for women who are in midwife-led compared to obstetrician-led care during labor. It will be a challenge to maintain the high level of experienced continuity of care in an integrated maternity care system. Experienced continuity of care seems to be a distinctive concept that should not be confused with experienced quality of care or perception of labor and should be considered as a complementary aspect of quality of care.